2011
DOI: 10.1007/s10792-011-9460-x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal collagen cross-linking using riboflavin and ultraviolet-A irradiation: a review of clinical and experimental studies

Abstract: Corneal collagen cross-linking (CXL) using riboflavin and ultraviolet-A irradiation is a common method of tissue stabilization and has been developed primarily to address the need of treating keratoconus. CXL's promising results on keratoconus indicated that it might be effective in other corneal diseases as well. This new treatment promises a slowing effect on the progression of these diseases and its initial results show that it is safe and reasonably curative. The purpose of this review is to critically eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 78 publications
0
28
0
2
Order By: Relevance
“…A nother hypothesis to consider is that the progression of keratoconus is explosive in children, w ith a short tim e betw een the onset of functional sym ptom s and the developm ent of a severe form of keratoconus. [16][17][18] T herefore, early detection of keratoconus in children w ith astigm atism is crucial because of the risk of rapid scalability, even at an early disease stage, close m onitoring of children is necessary in order to detect any sign of scalability and offer appropriate treatm ent. 19 C hatzis et al 3 found that 88% of pediatric keratoconic patients dem onstrated progression from their initial evaluation an d S o eters et al, 21 rep o rted rap id p ro gressio n o f th e keratoconus ranging from 2.6 D in several w eeks to 5.0 D over a year.…”
Section: Discussionmentioning
confidence: 99%
“…A nother hypothesis to consider is that the progression of keratoconus is explosive in children, w ith a short tim e betw een the onset of functional sym ptom s and the developm ent of a severe form of keratoconus. [16][17][18] T herefore, early detection of keratoconus in children w ith astigm atism is crucial because of the risk of rapid scalability, even at an early disease stage, close m onitoring of children is necessary in order to detect any sign of scalability and offer appropriate treatm ent. 19 C hatzis et al 3 found that 88% of pediatric keratoconic patients dem onstrated progression from their initial evaluation an d S o eters et al, 21 rep o rted rap id p ro gressio n o f th e keratoconus ranging from 2.6 D in several w eeks to 5.0 D over a year.…”
Section: Discussionmentioning
confidence: 99%
“…The light-induced production of oxygen radicals results in the formation of additional chemical bonds between collagen fibrils to induce stiffening of the cornea. [1][2][3][4] Although, the genesis aim of CXL procedure was the treatment of keratoconus, a role for CXL has also been suggested for other forms of corneal ectasia and a number of non-ectatic corneal diseases, such as infectious keratitis, bullous keratopathy, and corneal ulcers. 4 Bullous keratopathy, caused by endothelial dysfunction, leads to chronic corneal edema, epithelial bullae, recurrent erosions, and subsequent visual impairment and ocular discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…C orneal cross-linking (CXL) is an innovative approach to increase the mechanical and biochemical stabilities of the corneal stroma to halt keratoconus progression. [1][2][3] Although, the genesis aim of CXL procedure was the treatment of keratoconus, a role for CXL has also been suggested as a promising alternative method in managing bullous keratopathy by reducing ocular discomfort, increasing visual acuity and probably postponing or even eliminating the need for corneal transplantation. [4][5][6][7] In the present study we evaluated the effects of UVA CXL following intrastromal 0.1% riboflavin administration on quality of life in patients with bullous keratopathy.…”
Section: Effect Of Corneal Collagen Cross-linking On Quality Of Life mentioning
confidence: 99%
“…Recently, corneal repairs have been achieved using combined riboflavin UVA photoactivation treatment to strengthen collagen fibers types I, III and V through cross-linking and formation of collagen dityrosine [11,12,13,14]. This photopolymerization technique has also been reported for strengthening collagen in skin and knee cartilage [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies of POP have been extensively reviewed [5,6,7,8], and current evidence suggests an important etiology of POP is the degradation of collagen in vaginal tissues [9,10]. Interestingly, strengthening collagen fibers by cross-linking in collagen types I, III and V has been achieved using combined riboflavin UVA (365-370 nm) photoactivation treatment in corneal repairs [11,12,13,14]. This technique has been used for strengthening tissues [15,16] and involves exciting riboflavin to generate singlet oxygen molecules for inducing covalent bonds bridging the amino groups of collagen fibrils [17,18].…”
Section: Introductionmentioning
confidence: 99%